2014
DOI: 10.1542/hpeds.2014-0062
|View full text |Cite
|
Sign up to set email alerts
|

Bending the Value Curve

Abstract: In health care policy circles, "bending the cost curve down" may qualify as the phrase of the decade. More than 1 million web search references are testament to its widespread use, intended to express a focus on reducing health care costs. Yet it should not surprise anyone familiar with technocratic vocabulary that there is no clear agreement on what the phrase means. 1 Nonetheless, with health care spending nearing one-fi fth of the nation's gross domestic product, 2 the nationwide clamor to "bend the cost cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…15 A few successful projects have revealed that a focused HVC curriculum can be implemented, 16 although the development of such a curriculum can be extremely expensive and time consuming. Necessary educational resources are available through journal sections on value, 17,18 Choosing Wisely resources, 19 and various other HVC curricula. [20][21][22][23] Despite these resources, data reveal that only 10% of pediatric program directors and 15% of internal medicine residency programs report having a formal curriculum on HVC.…”
Section: Problem Identificationmentioning
confidence: 99%
“…15 A few successful projects have revealed that a focused HVC curriculum can be implemented, 16 although the development of such a curriculum can be extremely expensive and time consuming. Necessary educational resources are available through journal sections on value, 17,18 Choosing Wisely resources, 19 and various other HVC curricula. [20][21][22][23] Despite these resources, data reveal that only 10% of pediatric program directors and 15% of internal medicine residency programs report having a formal curriculum on HVC.…”
Section: Problem Identificationmentioning
confidence: 99%
“…10,11 Some physicians have even advocated for advancing HVC as a seventh core competency within the Accreditation Council for Graduate Medical Education's requirements. 12 In the past decade, we have made progress establishing needed educational resources around HVC with the introduction of journal sections on value, 13,14 the Choosing Wisely campaign, 15 and HVC curricula. [16][17][18][19] Despite this increase in resources, there remains a significant gap in uptake.…”
Section: Introductionmentioning
confidence: 99%
“…As the call for "bending the value curve" has echoed through hospital systems and training programs, it is essential that we not only teach trainees about health care value but also empower them to identify examples of low-value care and give them tools and resources to be a more effective part of the solution. 1 As part of the Hospital Pediatrics Bending the Value Curve series, we describe how low-value patient care stories such as the one above inspired a resident-led quality improvement (QI) initiative.…”
mentioning
confidence: 99%